Robert Lepage's original stage productions making theatre global - Fricker, Karen (Manchester [UK] Manchester University Press, 2020)
This book explores the development of Robert Lepage's distinctive approach to stage direction in the early (1984-1994) and middle (1995-2008) stages of his career, arguing that globalisation had a defining effect on shaping his aesthetic and his professional trajectory. In addition to globalisation theory, the book draws on cinema studies, queer theory, and theories of affect and reception. Each of six chapters treats a particular aspect of globalisation, using this as a means to explore one or more of Lepage's productions. Productions discussed include The Dragon's Trilogy, Needles and Opium, and The Far Side of the Moon. Making theatre global: Robert Lepage's original stage productions will be of interest to scholars of contemporary theatre, advanced-level undergraduates, and arts lovers keen for new perspectives on one of the most talked-about theatre artists of the early 21st century.
Includes bibliographical references and index.
Keywords: Theater and globalization; Theater -- Production and direction -- Que´bec (Province).